Terrorism Risk Concern in Europe - Konstantinos Drakos; Cathérine Müller (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We explore whether differences of terrorism risk perception across all European countries reflect their underlying differences in terrorism risk, which we decompose into a long term and innovation component. We employ longitudinal country-level data on terrorism risk concern and our modeling approach is motivated by the Bayesian framework. We conclude that the observed risk perception variation is significantly explained by the long term terrorism countries face, while the cyclical part of terrorism activity does not affect risk perception.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330